Outcomes of Induction Chemotherapy Plus Intensity-Modulated Radiotherapy (IMRT) Versus IMRT Plus Concurrent Chemotherapy for Locoregionally Advanced Nasopharyngeal Carcinoma: A Propensity Matched Study - Pu-Yun OuYang; Zhuo-Fei Bi; Lu-Ning Zhang; Kai-Yun You; Yao Xiao; Xiao-Wen Lan; Jie Tang; Xi-Cheng Wang; Wuguo Deng; Fang-Yun Xie (Translational Oncology, 2016)
PURPOSE: It deserves investigation whether induction chemotherapy (IC) followed by intensity-modulated radiotherapy (IMRT) is inferior to the current standard of IMRT plus concurrent chemotherapy (CC) in locoregionally advanced nasopharyngeal carcinoma. METHODS: Patients who received IC (94 patients) or CC (302 patients) plus IMRT at our center between March 2003 and November 2012 were retrospectively analyzed. Propensity-score matching method was used to match patients in both arms at equal ratio. Failure-free survival (FFS), overall survival (OS), distant metastasis–free survival (DMFS), and locoregional relapse–free survival (LRFS) were assessed with Kaplan-Meier method, log-rank test, and Cox regression. RESULTS: In the original cohort of 396 patients, IC plus IMRT resulted in similar FFS (P = .565), OS (P = .334), DMFS (P = .854), and LRFS (P = .999) to IMRT plus CC. In the propensity-matched cohort of 188 patients, no significant survival differences were observed between the two treatment approaches (3-year FFS 80.3% vs 81.0%, P = .590; OS 93.4% vs 92.1%, P = .808; DMFS 85.9% vs 87.7%, P = .275; and LRFS 93.1% vs 92.0%, P = .763). Adjusting for the known prognostic factors in multivariate analysis, IC plus IMRT did not cause higher risk of treatment failure, death, distant metastasis, or locoregional relapse. CONCLUSIONS: IC plus IMRT appeared to achieve comparable survival to IMRT plus CC in locoregionally advanced nasopharyngeal carcinoma. Further investigations were warranted.